2014
DOI: 10.1186/1471-2164-15-623
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation in PLD4 is associated with a zinc deficiency-like syndrome in Fleckvieh cattle

Abstract: BackgroundBovine hereditary zinc deficiency (BHZD) is an autosomal recessive disorder of cattle, first described in Holstein-Friesian animals. Affected calves suffer from severe skin lesions and show a poor general health status. Recently, eight calves with the phenotypic appearance of BHZD have been reported in the Fleckvieh cattle population.ResultsIn spite of the similar disease phenotypes, SLC39A4, the gene responsible for BHZD in Holstein-Friesian was excluded as underlying gene for the disorder in the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…The joint analysis of homozygosity depletion and insemination and rearing data revealed a 1.14 Mb haplotype located between 10,694,269 bp and 11,833,182 bp on BTA19 as the most likely interval harboring the causal mutation, which agrees with previous findings [17,19]. [10,18,26,30].…”
Section: Discussionsupporting
confidence: 90%
“…The joint analysis of homozygosity depletion and insemination and rearing data revealed a 1.14 Mb haplotype located between 10,694,269 bp and 11,833,182 bp on BTA19 as the most likely interval harboring the causal mutation, which agrees with previous findings [17,19]. [10,18,26,30].…”
Section: Discussionsupporting
confidence: 90%
“…Interest has become increasingly focused on PLD1 and PLD2 in the context of cancer, cardiovascular, neurodegenerative, and infectious disease, while loss of function of PLD3 has been linked to Alzheimer’s disease [7], loss of PLD4 function to autoimmune disease [4, 8, 9], and PLD6 has been found to be required for spermatogenesis [10]. Mice lacking PLD5 have been generated by the International Knockout Mouse Consortium program and subjected to a standardized phenotypic screen involving 25 tests, but no significant abnormalities were observed [11].…”
Section: Phospholipase D Superfamily Overviewmentioning
confidence: 99%
“…Recently, it was reported that the PLD4 gene is an indicator of susceptibility to certain autoimmune diseases in a Japanese population, 4) and a nonsense mutation in PLD4 gene was shown to cause a zinc deficiency-like syndrome in cattle. 5) However, the roles of PLD4 in these disorders as well as in normal brain development are still unknown.…”
Section: Introductionmentioning
confidence: 99%